2019
DOI: 10.1590/0074-02760190020
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of metallo-β-lactamase-encoding genes found in distinct species of Acinetobacter isolated from the Brazilian Amazon Region

Abstract: BACKGROUND The multidrug resistance (MDR) phenotype is frequently observed in Acinetobacter baumannii , the most clinically relevant pathogenic species of its genus; recently, other species belonging to the A. calcoaceticus-A. baumannii complex have emerged as important MDR nosocomial pathogens. OBJECTIVES The present study aimed to verify the occurrence of metallo-β-lactamase genes among distinct Acine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 18 publications
0
6
0
3
Order By: Relevance
“…Although reports of bla NDM in Latin America are limited, sentinel investigations have described the presence of Tn125 in Acinetobacter spp. (6,(15)(16)(17). An ST25 A. baumannii strain from a patient with an abdominal infection in Honduras was determined to have Tn125 on a plasmid (18), but this plasmid was not present in the ST25 strains analyzed here.…”
mentioning
confidence: 78%
“…Although reports of bla NDM in Latin America are limited, sentinel investigations have described the presence of Tn125 in Acinetobacter spp. (6,(15)(16)(17). An ST25 A. baumannii strain from a patient with an abdominal infection in Honduras was determined to have Tn125 on a plasmid (18), but this plasmid was not present in the ST25 strains analyzed here.…”
mentioning
confidence: 78%
“…In Brazil, KPC has become endemic and widely disseminated among K. pneumoniae from hospitals in all Brazilian regions [ 5 , 14 , 17 , 20 , 21 , 27 , 28 , 29 , 30 ]. Since 2013, NDM-producing isolates have been reported in different Brazilian regions and associated with a wide variety of bacterial species, including Escherichia coli , Acinetobacter baumannii , A. nosocomialis , A. pittii, Enterobacter cloacae, Enterobacter hormaechei, and K. pneumoniae [ 12 , 15 , 16 , 31 , 32 , 33 , 34 , 35 ]. Recently, Silva et al [ 16 ], in a study evaluating 81 bacterial isolates from different regions, demonstrated that K. pneumoniae is responsible for the widespread of this carbapenemase in Brazilian hospitals, confirming more efficient dissemination compared with the bla KPC variant.…”
Section: Discussionmentioning
confidence: 99%
“…nosocomialis e A. baumannii (PILLONETTO et al, 2014;CHAGAS et al, 2015;PAGANO et al, 2015;BRASILIENSE et al, 2019 (HIGGINS et al, 2013). No Brasil, OXA-23 é a principal oxacilinase responsável pela resistência aos carbapenêmicos em amostras hospitalares (DALLA-COSTA et al, 2003;CARVALHO et al, 2009;MARTINS et al, 2009;MOSTACHIO et al, 2009;ROYER et al, 2015).…”
Section: Lista De Abreviaturas Siglas E Símbolosunclassified
“…Curiosamente, as duas cepas foram isoladas em 2016 e os pacientes tinham doenças neurológicas, no entanto, as cepas estavam geograficamente distantes a 2.330,4 km (BRASILIENSE et al, 2019). Outro plasmídeo idêntico foi relatado em A. baumannii nos EUA, em 2018, sugerindo a circulação desse plasmídeo no continente americano contendo uma variante do Tn125 em Acinetobacter sp., uma vez que não foi encontrado no GenBank plasmídeo semelhante em isolados da Europa e somente um na Ásia.…”
Section: Tabelaunclassified
See 1 more Smart Citation